2019
DOI: 10.1111/ele.13378
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen limitation inhibits marine diatom adaptation to high temperatures

Abstract: Ongoing climate change is shifting species distributions and increasing extinction risks globally. It is generally thought that large population sizes and short generation times of marine phytoplankton may allow them to adapt rapidly to global change, including warming, thus limiting losses of biodiversity and ecosystem function. Here, we show that a marine diatom survives high, previously lethal, temperatures after adapting to above‐optimal temperatures under nitrogen (N)‐replete conditions. N limitation, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…For the annual kelp Undaria pinnatifida, Gao et al 55 found differences in the thermal tolerance of geographically separated populations, where individuals with a higher thermal tolerance had the greatest capacity to store N. These results support our hypothesis that populations of Macrocystis that are naturally exposed to greater N supply will have a greater thermal tolerance than that those exposed to limiting nutrient concentrations. For microalgae, it is well documented that they are more vulnerable to high temperatures under N limited conditions compared to N-sufficient ones 73,74 . However, further studies comparing the effects of www.nature.com/scientificreports www.nature.com/scientificreports/ nitrogen and/or other local drivers on the thermal plasticity of populations separated geographically are urgently required to more precisely predict species' responses to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…For the annual kelp Undaria pinnatifida, Gao et al 55 found differences in the thermal tolerance of geographically separated populations, where individuals with a higher thermal tolerance had the greatest capacity to store N. These results support our hypothesis that populations of Macrocystis that are naturally exposed to greater N supply will have a greater thermal tolerance than that those exposed to limiting nutrient concentrations. For microalgae, it is well documented that they are more vulnerable to high temperatures under N limited conditions compared to N-sufficient ones 73,74 . However, further studies comparing the effects of www.nature.com/scientificreports www.nature.com/scientificreports/ nitrogen and/or other local drivers on the thermal plasticity of populations separated geographically are urgently required to more precisely predict species' responses to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, larger grazers, such as mesozooplankton, which were excluded in our study, can be less susceptible to thermal stress than phototrophs (Liu et al, 2019). In addition, nutrient availability, which was fixed in our mesocosms, may alter the net impact of future scenarios because nutrient limitation has been shown to reduce the thermal dependence of phytoplankton metabolic rates (O'Connor et al, 2009;Marañón et al, 2018), cause a lower thermal resilience in phytoplankton populations (Thomas et al, 2017), and even inhibit adaptation to high temperatures over evolutionary time scales (Aranguren-Gassis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…without diurnal or seasonal fluctuations in temperature and/or pCO 2 ), experimental evolution studies of marine dinoflagellates, diatoms and coccolithophores under high temperature and/or pCO 2 conditions have mostly resulted in adaptation to the new environment (Table 1). Thus, fitness gains have been demonstrated in traits as diverse as cell growth (Aranguren-Gassis et al, 2019;Benner et al, 2020;Buerger et al, 2020;Chakravarti et al, 2017;Chakravarti & van Oppen, 2018;Huertas et al, 2011;Hutchins et al, 2015;Jin et al, 2013;Lohbeck et al, 2012;O'Donnell et al, 2018;Schaum et al, 2018), polyunsaturated fatty acid content (O'Donnell et al, 2019), photo-physiological performance and extracellular ROS level (Buerger et al, 2020;Chakravarti et al, 2017;Chakravarti & van Oppen, 2018). For example, populations of the marine diatom Thalassiosira pseudonana evolved under elevated temperature (32°C) achieved similar growth rates at high temperature compared to wild-type cells grown under control temperature (22°C) after ~100 asexual generations (Schaum et al, 2018).…”
Section: Studies Showing Increased Fitness Following Experiments Evolutionmentioning
confidence: 99%
“…simplex evolved at high temperature under both N-limited and Nreplete conditions for 200 generations grew faster than the control populations at 32°C, only the populations evolved under N-replete conditions were able to survive in 75% of the trials and grow without delay under 34°C (Table 1; Aranguren-Gassis et al, 2019). In other words, nitrogen limitation may preclude thermal adaptation.…”
Section: Tr Ade-offsmentioning
confidence: 99%
See 1 more Smart Citation